Fundamentals of soft matter science - Hirst, Linda S (CRC Press, 2013)
"The properties of everyday soft materials such as polymers, rubbers, gels, colloids, and liquid crystals that touch every aspect of our lives cannot be understood without an introduction to the fundamental science behind molecular self-assembly and the physics of these materials. Designed to provide an introduction for mid to upper-level undergraduates, this book can also provide useful resource for graduate students or more senior scientists of all levels new to the field of soft matter"